(untitled) (International Journal of Food and Nutritional Sciences, 2022)
One facet of this evolution is the emergence of thin films, which are not two-dimensional due to the dimensional growth constraint. This has several uses across various fields. Variety of materials, including metals, semiconductors, insulators, dielectrics, and many more, may be used to make thin films, and they can be manufactured in a number of different methods. There are several suggested methods for the configuration of films. The deposited quality with the least degree of compositional change [1] and the most repeatable characteristics can also be improved using new techniques. With the right thin film production procedure, thin film properties and flexibility may be obtained. Chemical deposition techniques are commonly used to make thin films because of their adaptability in depositing a wide range of compounds, as well as their ability to control synthesis parameters at low deposition temperatures [2-3].